Systematic review: Outcome reporting bias is a problem in high impact factor neurology journals. - Benjamin Howard; Jared T Scott; Mark Blubaugh; Brie Roepke; Caleb Scheckel; Matt Vassar (PLoS ONE, 2017)
Background Selective outcome reporting is a significant methodological concern. Comparisons between the outcomes reported in clinical trial registrations and those later published allow investigators to understand the extent of selection bias among trialists. We examined the possibility of selective outcome reporting in randomized controlled trials (RCTs) published in neurology journals. Methods We searched PubMed for randomized controlled trials from Jan 1, 2010 -Dec 31, 2015 published in the top 3 impact factor neurology journals. These articles were screened according to specific inclusion criteria. Each author individually extracted data from trials following a standardized protocol. A second author verified each extracted element and discrepancies were resolved. Consistency between registered and published outcomes was evaluated and correlations between discrepancies and funding, journal, and temporal trends were examined. Results 180 trials were included for analysis. 10 (6%) primary outcomes were demoted, 38 (21%) primary outcomes were omitted from the publication, and 61 (34%) unregistered primary outcomes were added to the published report. There were 18 (10%) cases of secondary outcomes being upgraded to primary outcomes in the publication, and there were 53 (29%) changes in timing of assessment. Of 82 (46%) major discrepancies with reported p-values, 54 (66.0%) favored publication of statistically significant results. Conclusion Across trials, we found 180 major discrepancies. 66% of major discrepancies with a reported p-value (n = 82) favored statistically significant results. These results suggest a need within neurology to provide more consistent and timely registration of outcomes.